MANFAAT PENDIDIKAN KESEHATAN REPOSISI DAN MINYAK KELAPA TERHADAP PENCEGAHAN DEKUBITUS - Amik Muladi, S.Kep.Ns, Betty Sunaryanti, S.Kep.Ns., M.Kes, (PROSIDING, 2014)
Background: The results Kurniawan(2009) demonstrate knowledge of the meaning of decubitus nurses 66.7%, 59% prevention purposes, and prevention of pressure sores 51.3%. The prevalence of pressure sores were reported in homes in the range of 12.9% to 19% (Potter andPerry., 2005).Suheri research results (2009) showed that thelength of stayin the occurrence of decubitus so reson patient immobilizati on decubitus sores 88.8% with an average length of stay on the fifth day oftreatment.Purpose: to determine the benefits of health education repositioning with coconutoil.Methods: This studyis aquantitati vestudy with Randomize Controlled Trial. Assessment of patients using the Norton scale assessment. Research will be held for 7days. Statistical testtouse thet-test.Referrals: The results wer every influential studyis the provision of health education to the community about reposition ingcoupled with feeding coconut oil with p: 0.015, through proceedings publications and text books.Keywords: healtheducation, coconutoil, decubitus